2016
DOI: 10.1111/1365-2745.12574
|View full text |Cite
|
Sign up to set email alerts
|

Where, why and how? Explaining the low‐temperature range limits of temperate tree species

Abstract: 1. Attempts at explaining range limits of temperate tree species still rest on correlations with climatic data that lack a physiological justification. Here, we present a synthesis of a multidisciplinary project that offers mechanistic explanations. Employing climatology, biogeography, dendrology, population and reproduction biology, stress physiology and phenology, we combine results from in situ elevational (Swiss Alps) and latitudinal (Alps vs. Scandinavia) comparisons, from reciprocal common garden and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(150 citation statements)
references
References 94 publications
(163 reference statements)
6
143
1
Order By: Relevance
“…Phenology controls also set the termination of growth activity in autumn before damaging freezing temperatures come into action. Plants adapted to cold climates must be able to complete their seasonal life cycle within the time frame set by phenology controls 10 . During the dormant period, long-lived plants native to cold climates have gone through evolutionary selection and thus are commonly safe from fatal freezing damage; some even survive dipping in liquid nitrogen during the coldest part of the year.…”
Section: Evolutionary Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenology controls also set the termination of growth activity in autumn before damaging freezing temperatures come into action. Plants adapted to cold climates must be able to complete their seasonal life cycle within the time frame set by phenology controls 10 . During the dormant period, long-lived plants native to cold climates have gone through evolutionary selection and thus are commonly safe from fatal freezing damage; some even survive dipping in liquid nitrogen during the coldest part of the year.…”
Section: Evolutionary Adaptationmentioning
confidence: 99%
“…As a result, trees are able to develop mature, winter-hardy tissues. The required minimum season length is determined by life history traits such as fruit size and wood anatomy 10 .…”
Section: Ecology Of Freezing Resistancementioning
confidence: 99%
“…A recent study has shown the phylogenetic basis of the vulnerability to late frost events using 170 woody species growing in an arboretum in Germany, and suggests a tight link between the natural distribution range of a given species and its winter cold hardiness (Muffler et al ., ). However, the influence of spring phenology on the growing season length has been reconsidered recently as a key potential factor limiting the upper elevation limit of temperate tree species growing below the treeline (Körner et al ., ). The authors demonstrated by an array of experiments and in situ monitoring that, at the cold edge of species distribution, avoiding frost damage in spring by delaying phenology occurs at the cost of a dramatic reduction in the growing season, leaving too short a time for the complete maturation of cold hardy tissues (Körner et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…forest fires, wind throw, topography, soil characteristics, interspecific competition and successional stage) mostly overrule the importance of regional climate (Pearson and Dawson 2003;Körner et al 2016;Kuosmanen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Just as everywhere else on our planet, Russian forests are generally shaped by a combination of various factors, which can be divided into four principal groups: historic, current abiotic, biotic and anthropogenic (Huston 1994). It is recognized that the modern differentiation of the tree species composition on a latitudinal gradient is determined primarily by climate (Sykes et al 1996;Körner et al 2016;Vetluzhskikh 2016), and for boreal and northern temperate European forests the most important factor is temperature (Morozova 2009). However, other factors acting on different spatial scales may have a significant impact on the local patterns of tree species richness (Caley and Schluter 1997;Svenning and Skov 2005;Svenning et al 2010).…”
Section: Introductionmentioning
confidence: 99%